Quantification of Geographic Atrophy Using Spectral Domain OCT in Age-Related Macular Degeneration - Cleland, Spencer C; Konda, Sri Meghana; Danis, Ronald P; Huang, Yijun; Myers, Dawn J; Blodi, Barbara A; Domalpally, Amitha (Ophthalmology retina, 2021)
To compare geographic atrophy (GA) area and enlargement rate measured with spectral domain OCT (SD-OCT) with fundus autofluorescence (FAF), color fundus photography (CFP), and infrared reflectance (IR) imaging. Retrospective, multicenter, natural history case series. A total of 70 eyes with GA from 48 participants were included. Participants underwent SD-OCT, FAF, CFP, and IR imaging at baseline and 12 months in the study eye. Spectral domain OCT images were graded for GA area using 2 distinct criteria: (1) complete retinal pigment epithelium and outer retinal atrophy (cRORA) and (2) hypertransmission through Bruch's membrane. Areas were measured with SD-OCT using a custom-developed tool that allows for mapping areas of retinal layer loss on SD-OCT cross-sectional scans with co-registered IR images. Circularity index was calculated from area and perimeter. Spectral domain OCT images were also assessed for presence of reticular pseudodrusen, outer-retinal tubules, and hyporeflective wedge-shaped bands. Area of GA was measured in millimeters squared from FAF, CFP, and IR images. Geographic atrophy mean baseline area and enlargement rate measured with 2 SD-OCT criteria, FAF, CFP, and IR. At baseline, the mean GA area was 6.9 (standard deviation [SD], 4.7) mm using the SD-OCT cRORA criteria and 7.3 (SD, 4.7) mm using the SD-OCT hypertransmission criteria. The mean annual enlargement rate of GA was 1.6 (SD, 1.1) mm using the SD-OCT cRORA criteria and 1.5 (SD, 1.0) mm using the SD-OCT hypertransmission criteria. When comparing both SD-OCT grading criteria with FAF, CFP, and IR, there were no statistically significant differences in baseline area or annual enlargement rate of GA. Circularity index was identified as the risk factor for increased annual enlargement rate. Measuring GA using retinal layer morphology provides a novel means of obtaining area measurements. Area measurements tend to vary based on criteria used and are comparable to other imaging modalities.